Предмет: Алгебра, автор: b124126120776727

Вычислите 5^-8*5^10-7^-5:7^-5 ((3/4)^2)^-1

Приложения:

b124126120776727: Добавил

Ответы

Автор ответа: Аноним
0

Ответ:

5 {}^{ - 8}  \times 5 {}^{10}  -  {}^{ - 5}   \div 7 {}^{ - 5}  + (( \frac{3}{4}) {}^{2}  ) {}^{ - 1}  = 5 {}^{2}  - 7 {}^{ - 5}  \div 7 {}^{ - 7}  + (( \frac{3}{4} ) {}^{2} ) {}^{ - 1}  = 5 {}^{2}  - 1 + (( \frac{3}{4} ) {}^{2} ) {}^{ - 1}  = 5 {}^{2}  - 1 + ( \frac{3}{4} ) {}^{ - 2}  = 25 - 1 + ( \frac{ 3}{4}  {}^{ - 2}  = 25 - 1 +  ( \frac{4}{3} ) {}^{2}  = 24 + ( \frac{4}{3} ) {}^{2}  = 24 +  \frac{16}{9}  =  \frac{238}{9}

Ответ -

 \frac{232}{9}

Похожие вопросы
Предмет: Математика, автор: matosastanislav
Предмет: Математика, автор: ириска91